The STAT3-Ser/Hes3 signaling axis in cancer - Poser, Steven; Park, Deric M.; Androutsellis-Theotokis, Andreas (Frontiers in Bioscience, 2014)
Disrupting the regenerative capacity of tumorigenic cells is a major focus in medicine. These regenerative properties are carried by a subpopulation of cells within the tumor, termed cancer stem cells. Current therapies don't effectively tackle the disease suggesting these cells employ yet unidentified molecular mechanisms allowing them to evade targeting. Recent observations in neural stem cells reveal an extraordinary plasticity in the signaling pathways they utilize to grow. These findings are being extended to the cancer stem cell field, illuminating conceptually novel treatment strategies. Tumorigenic cells can make use of distinct, even opposing pathways, including JAK/STAT and the non-canonical STAT3-Ser/Hes3 signaling axis. This plasticity may not be confined to the cancer stem cell population, but may be shared by various cell types within the tumor, blurring the line distinguishing cancer stem cells from other tumor cell types. The implications to anti-cancer medicine are highly significant, since these findings demonstrate that inhibiting one cell growth pathway may actually enhance the activity of alternative ones. Drug discovery programs will also benefit from these concepts.